Fen ecohydrologic trajectories in response to groundwater drawdown with an edaphic feedback. Issue 8 (29th August 2022) - Booth, Eric G.; Loheide, Steven P.; Bart, David
Abstract: Fens are high conservation value ecosystems that depend on consistent discharge of groundwater that saturates the near surface for most of the growing season. Reduced groundwater inputs can result in losses of native diversity, decreases in rare‐species abundance and increased invasion by non‐native species. As such, fen ecosystems are known to be particularly susceptible to changes in groundwater conditions including reduction in water levels due to nearby groundwater pumping. However, research is lacking on whether floristic degradation is influenced by feedbacks between hydrology and soil properties. We present a model of an archetype hillslope fen that couples a hydrological niche model with a variably saturated groundwater flow model to predict changes in vegetation composition in response to different groundwater drawdown scenarios. The model explores a potential edaphic feedback through the use of an observed relationship between fen floristic quality and soil/peat water retention characteristics that is attenuated with separate edaphic and floristic memory terms representing lags in biophysical responses to dewatering. Model parameters were determined based on data collected from six fens in Wisconsin under various states of degradation. We observed different water retention characteristics between sites that were minimally impacted versus degraded that are likely due to peat decomposition, oxidation and compaction at the degraded sites. These characteristics were also correlated with floristic quality. The results reveal a complex response to drawdown where changes in peat hydraulic properties following dewatering lead to even drier conditions and further shifts away from typical fen species.